NEW ENTITIES ON THE FINANCIAL MARKET — FINTECH, BIGTECH AND NEOBANK — REGULATION PROPOSAL - Фольварський, Матеуш (Socio-economic relations in the digital society, 2020)
Digitization of financial services and a decrease in trust in traditional financial institutions allow the emergence of new entities that provide services which were traditionally reserved for banks. FinTechs, BigTechs and neo-banks significantly affect the decline in revenues of traditional financial institutions. New entities, however, are not covered by such regulations as banks, and market regulators very often do not have instruments to supervise these companies. The article proposes to create lists of systemically important FinTechs, BigTechs and neobanks that can significantly affect financial stability.
Keywords: FinTech; BigTech; neobank; regulation